Potential of novel feed efficiency traits for dairy cows based on respiration gas exchanges measured by respiration chambers or GreenFeed - Huhtanen, Pekka; Bayat, Ali-Reza (Elsevier, 2025)
Residual feed intake (RFI), calculated as a difference between observed and predicted intake, is a commonly used estimate of feed efficiency (FE). Determination of FE in practical dairy herds is challenging, as it requires accurate estimation of feed intake of individual cows. Alternatively, FE could be estimated as a difference between observed and predicted metabolic losses derived from gas exchanges. The objectives were to compare respiration chambers (RC) and the GreenFeed (GF) system in estimating FE based on the gas data, and to compare FE estimated from measured feed intake or gas data. The study was conducted using 32 Nordic Red dairy cows (DIM 159 ± 63, BW 634 ± 60 kg, and milk yield 28.9 ± 6.7 kg/d) fed a grass silage-based diet (CP 152 g/kg DM, NDF 395 g/kg DM). The study included two 14-d periods with the GF system with a 1-wk period in RC chambers (3-d measurements) between the GF periods. Residual CO2 production (RCO2), residual O2 consumption (RO2) and residual heat production (RHP) were estimated as observed minus predicted values derived from energy requirements. Root means squared errors of DMI prediction were smaller for models based on CO2 or O2 and ECM yield compared with ECM + BW model both with RC and GF data with minor differences between the methods. The relationship between GF and RC was slightly better for RO2 (R2 = 0.68) and RHP (R2 = 0.67) compared with RCO2 (R2 = 0.59). Seventy-five percent of the top 50% (12/16) cows in GF were ranked among the top 50% in RC. Repeatability values of different FE traits were similar or higher for the data based on gas data measured by GF compared with the corresponding values based on measured feed intake. Residual CO2 production explained 57% of variation in residual ME intake (RMEI). Gross FE expressed as ECM/CO2 explained 82% of gross FE expressed as ECM/DMI. When the cows were divided into low, medium, and high RCO2 groups, the differences in various FE traits were consistent with those based on measured feed intake. The difference in RMEI between the Low- and High-RCO2 cows was 15 MJ/d. Low-RCO2 cows produced 13% less methane per kilogram ECM, had higher diet digestibility, and produced less heat than high-RCO2 cows. It is concluded that estimating FE from gas data measured by the GF system has a potential to rank the cows according to FE in farm conditions without requiring measuring feed intake.
Keywords: residual gas exchanges; residual heat production; measurement techniques; feed efficiency